Comparative analysis of the functional state of the cardiovascular system of underwater swimmers in different time periods - E.V. Redi, (Theory and Practice of Physical Culture, 2023)
Objective of the study was a comparative assessment of the functional state of the cardiovascular system of underwater swimmers in different time periods. Methods and structure of the study. The survey involved highly qualified underwater athletes, members of the national team of the Krasnoyarsk Territory (2004, 2014, 2022), 10 girls, 10 boys. The study was conducted at the sports bases of the city of Krasnoyarsk (sports complex "Avangard", "Water Sports Palace of the Siberian State University"). The following methods were used in the work: analysis of pedagogical and scientific-methodical literature, methods for assessing anthropometric indicators (measurement of body length, measurement of body weight, measurement of chest circumference, measurement of hand strength, calculation of weight-height index, calculation of life index), methods for assessing morphofunctional indicators (heart rate, systolic blood pressure). Results and conclusions. The study made it possible to summarize that women involved in underwater sports in 2022 have higher indicators characterizing the morphological and functional capabilities of the body. They are taller, have the greatest weight, wrist muscle strength, higher weight-to-height index (WHI), life index (LI), resting heart rate (HR) than the athletes of 2004 and 2014. In men, the same trend persists, there is an increase in weight, height, hand strength, VHI, LI, heart rate at rest.